On some classes of hypergroups. Issue 1 (1st January 2018) - Aghabozorgi, H.; Jafarpour, M.; Davvaz, B.
Abstract: In this paper, we first introduce the notion of power(ful) hypergroups, proving that the classes of cancelative semigroups and complete hypergroups are powerful hypergroups. We investigate some properties of this class of (semi)hypergroups.